An economic evaluation of the Thai-New Zealand feeder road in Northeast Thailand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science - Askwith, John E (Massey University, 1973)
Transport has been identified as an essential element in a comprehensive regional development programme and economic, social, and political benefits can result from the construction of a road in a developing region. This study investigates the economic impact of a road construction project in Northeast Thailand. The Thai-New Zealand feeder road, a 144 kilometre paved road, was completed in 1971 and links five major towns in two provinces while passing through a region of populated villages. Nearly all households in this region engage in agricultural production. The rice crop is the most important factor affecting the welfare of a household and the quantities of produce sold from other enterprises are small. Purchased inputs, aside from small quantities of fertilizer, are not commonly used. This study has been undertaken only two years following completion of the road, although the first 36 kilometre section had been completed five years. The collection of data from households in villages adjacent to the road is deserined and the data obtained is discussed in relation to the characteristics and measurements of subsistence agriculture. Traffic usage of the road was measured in two surveys and a land classification survey was conducted to estimate the agricultural development that has taken place since road construction began. A large part of the study is devoted to a description of the agricultural enterprises practised in the region, the problems preventing economic development, and the potential for further development following construction of the Thai-New Zealand feeder road. This data has been used to assess the impact of the road at the present time and the likely impact under various conditions which might eventuate in the future. Methodology for a standard benefit-cost analysis has been used in the evaluation of the road. The three economic criteria, net present value, benefit-cost ratio, and project internal rate of return have been applied to the discounted cost and benefit flows. Together with those items that can not be quantified, these three criteria have been used to evaluate the profitability of the project. Construction of the Thai-New Zealand feeder road should be regarded as the provision of one input essential for economic development in the region. Other inputs will be necessary before the full benefit of the road can be obtained. The road has already had a significant economic impact and if the potential from the application of improved technology and practices within existing agricultural enterprises can be realised, the road will have an even greater role in the economic development of the region.
Keywords: Economic assistance; Roads - Thailand; New Zealand